The Ruamano Project: Raising Expectations, Realising Community Aspirations and Recognising Gifted Potential in Māori Boys - Webber, Melinda; Riley, Tracy; Sylva, Katrina; Scobie-Jennings, Emma (The Australian Journal of Indigenous Education, 2020)
When gifted Māori students feel they belong and find their realities reflected in the curriculum, conversations and interactions of schooling, they are more likely to engage in programmes of learning and experience greater school success. This article reports on a teacher-led project called the Ruamano Project, which investigated whether Maker and Zimmerman's (2008) Real Engagement in Active Problem Solving model (REAPS) could be adapted successfully to identify talents and benefit the student achievement and engagement of Māori boys in two rural Northland, New Zealand secondary school contexts. The project aimed to implement Treaty of Waitangi-responsive and place-based science practices by improving home–school–community relationships through the authentic engagement of whānau and iwi into the schools’ planning, implementation and evaluation of a REAPS unit. As a result of this innovation, teachers’ perceptions of Māori boys shifted, their teaching practices changed, more junior secondary Māori boys were identified as gifted by way of improved academic performance, and iwi and community members were engaged in co-designing the inquiry projects. Our research indicated that the local adaptation of the REAPS model was effective in engaging and promoting the success of gifted and talented Māori boys.